2018
DOI: 10.3390/en11020457
|View full text |Cite
|
Sign up to set email alerts
|

Suitability Evaluation of Specific Shallow Geothermal Technologies Using a GIS-Based Multi Criteria Decision Analysis Implementing the Analytic Hierarchic Process

Abstract: Abstract:The exploitation potential of shallow geothermal energy is usually defined in terms of site-specific ground thermal characteristics. While true, this assumption limits the complexity of the analysis, since feasibility studies involve many other components that must be taken into account when calculating the effective market viability of a geothermal technology or the economic value of a shallow geothermal project. In addition, the results of a feasibility study are not simply the sum of the various fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 36 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…The researchers stated that the use of the OWA method provided a model for generating prospective geothermal maps with different optimistic and pessimistic strategies. Tinti et al [41] used a GIS framework and the AHP method to assess the suitability of shallow geothermal technologies. This study, which involved comparing a large number of shallow geothermal source-related criteria and factors, reported that it was possible that one can draw a suitability map of technologies for Europe using the AHP method.…”
Section: Mcdm Methods In the Assessment Of Geothermal Projectsmentioning
confidence: 99%
“…The researchers stated that the use of the OWA method provided a model for generating prospective geothermal maps with different optimistic and pessimistic strategies. Tinti et al [41] used a GIS framework and the AHP method to assess the suitability of shallow geothermal technologies. This study, which involved comparing a large number of shallow geothermal source-related criteria and factors, reported that it was possible that one can draw a suitability map of technologies for Europe using the AHP method.…”
Section: Mcdm Methods In the Assessment Of Geothermal Projectsmentioning
confidence: 99%
“…Data on the geology of the area, ambient temperature and amplitude, geothermal heat fl ow, thermal conductivity of sediments and bedrock, thermal diffusivity of sediments and bedrock and thickness of sediments were known for the four selected points with a precision of 1 km ×1 km grid (Tinti et al, 2018). The ground temperature profi les were calculated using Equation 1, without taking into consideration any SUHI effect.…”
Section: The Impact Of Urban Heat Islandmentioning
confidence: 99%
“…Computational procedures [22] and numerical models and simulations have been developed by different authors [23e27] to allow simulation and design of systems. But to allow an overall assessment, the question about the site-specific potential of the technology is critical, where climatic, building type and underground site-specific information become key when it comes to assessing SGE potential [25,28,29]. Regarding policy decisions, additional local variables must be taken into account, such as environmental benefits or closeness to the resource to be exploited, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, so far, methodologies assessing spatial SGE suitability or/ and SGE potential developed in Europe cover a broad variety of scales, from small areas (plots to cities) [23,26,35] to larger ones (from regions to countries) [24,36]. Very little literature covers continental areas [29,37] whilst most studies are focused on a regional scale.…”
Section: Introductionmentioning
confidence: 99%